2012
DOI: 10.1186/1746-1596-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry profiles of breast ductal carcinoma: factor analysis of digital image analysis data

Abstract: BackgroundMolecular studies of breast cancer revealed biological heterogeneity of the disease and opened new perspectives for personalized therapy. While multiple gene expression-based systems have been developed, current clinical practice is largely based upon conventional clinical and pathologic criteria. This gap may be filled by development of combined multi-IHC indices to characterize biological and clinical behaviour of the tumours. Digital image analysis (DA) with multivariate statistics of the data ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 44 publications
8
56
1
Order By: Relevance
“…Similar results were shown by Patani et al who found that high SATB1 expression levels occurred more often in ERnegative cancers [29]. Towards to this observations, the use of SATB1 as target or prognostic marker for breast cancer should be viewed with caution and a possible confounding effect of the estrogen receptor status of the tumor should be taken into account when analyzing the diagnostic and prognostic value of SATB1 [30,37].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Similar results were shown by Patani et al who found that high SATB1 expression levels occurred more often in ERnegative cancers [29]. Towards to this observations, the use of SATB1 as target or prognostic marker for breast cancer should be viewed with caution and a possible confounding effect of the estrogen receptor status of the tumor should be taken into account when analyzing the diagnostic and prognostic value of SATB1 [30,37].…”
Section: Discussionsupporting
confidence: 57%
“…The authors focused on clinical application of results, so they analyzed expression of markers according to the status of hormone. They implied that SATB1 and HIF-1a may be important markers of the disease associated with ER-positive cancers, whereas their biological and clinical significance remains to be elucidated [30]. Their findings seem to be contrary to our data since we found moderate correlation between expression of SATB1 and Ki-67 in ER-negative tumors.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…As compared to the luminal A tumours, they may have a higher proliferation rate, they may express genes that seem to be shared with the basal-like and the Her-2 subtypes and they are associated with a less favourable outcome [8,9]. The high Ki67/ER factor scores were strongly associated with the higher grade and the luminal B type of tumours, but they were also detected in a set of grade1and luminal A cases , thus potentially indicating the high risk patients in these categories [10].…”
Section: Discussionmentioning
confidence: 94%